APPROACHES TO THE LIPID METABOLISM GENES POLYMORPHYSM ANALYSIS IN SCREENING FOR ATHEROSCLEROSIS RISK FACTORS - N. V. Koch; G. I. Lifschitz; E. N. Voronina (Российский кардиологический журнал)
The review concerns he etiology of polygenic hyperlipidemias. The most prominent and prevalent in more than 1% of inhabitants genetic markers are discussed. The mechanisms of minor alleles influence on the hypercholesterolemia are shown: APOAI 75G>A (rs670), CETP (rs5882), LIPC (rs1800588), APOE (E2/E3/E4), hypertrigliceridemia: APOA5 (rs3135506), FABP2 rs1799883, LPL rs328. Also the genetic markers discussed that influence food-seeking behavior and by various ways do increase daily fat intake: CD36 (rs1761667), FTO (rs8050136), MC4R (rs17782313). Carrying of several pathologic alleles in a patients does significantly increase the risk of primary hyperlipidemias. More studies needed to evaluate the effect of different genetic markers combination to invent these tests as an instrument of personified predictive medicine in clinical practice.